Albania : Second Post-Program Monitoring Discussions-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2019)
Growth was strong in 2018, backed by high electricity production. Inflation remains subdued, notwithstanding very accommodative monetary conditions. The fiscal stance in 2018 was somewhat tighter than expected, supporting a further decline in public debt. The medium-term economic outlook is broadly favorable, with growth projected to converge to 4 percent and a further narrowing of the current account deficit. However, significant risks remain. Growth is vulnerable to a continued or sharper economic slowdown in the main trading partners. The main vulnerabilities remain in the fiscal sector, as public debt is still high, and contingent liabilities are increasing. Albania's relatively large financing needs also pose risks that could materialize, in particular, in case of tightening external financing conditions.